Thanks Jacques! - Baldensperger, Jacques (Technical Centre for Agricultural and Rural Cooperation, 2000)
After more than five years of energetic service, Dr Jacques Baldensperger retired from CTA in December 1999. For many years a soil microbiologist in Senegal, Jacques was long associated with the French research organisation ORSTOM (now IRD). He...